Microwave imaging via implementation of capon beamforming algorithm for breast cancer detection - Chung, Jun Yien. (2009)
The conventional Delay and Sum (DAS) is the simplest and most commonly used method to obtain a microwave imaging. Recently proposed CAPON algorithms stated that it provide a better resolution and much better interference rejection capability than DAS. There are a few CAPON methods being proposed for Microwave Imaging which claims to be an improvement over another. Among these that we have chose to discuss later is Standard Capon Beamforming (SCB), weighted Capon Beamforming (WCB), Robust Capon Beamforming (RCB) and Robust Weighted Capon Beamforming(RWCB). In this context, we will investigate the implementation of several CAPON methods on breast tissue phantom for breast tumor detection. We will also compare it with DAS and discuss the result of these different methods.